The Effect of Absorptive Capacity and Innovation Strategy on Indonesian SMEs’ Performance with Open Innovation as the Mediator - Arifin, Nur Rohman; Hartono, Arif (International Review of Management and Marketing, 2025)
This study aims to examine the effect of absorptive capacity (ACAP) and innovation strategy (IS) on SME performance with open innovation (OI) as a mediator. The study was conducted among 200 SMEs in Yogyakarta Province, Indonesia. Data were collected through a quantitative approach, both online and offline surveys. Data is analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results show that absorptive capacity positively affects open innovation, improving SME performance. The findings also indicate that innovation strategy directly affects open innovation, but the direct effect on SME performance is insignificant. In contrast, open innovation is a significant mediator in the relationship between absorptive capacity and SME performance and between innovation strategy and SME performance. This research provides a practical contribution to SMEs' optimization of their innovation strategy by focusing on improving absorptive capacity and implementing open innovation to improve performance. The theoretical implications of this research enrich the literature on absorptive capacity, open innovation, and innovation strategy in the context of SMEs in developing countries.